2021
DOI: 10.3390/jcdd8110142
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose of Direct Oral Anticoagulants after Left Atrial Appendage Occlusion

Abstract: The optimal antithrombotic strategy following left atrial appendage occlusion (LAAO) is not yet clearly established. Low-dose non-vitamin K antagonist oral anticoagulants (NOAC) might represent a valid alternative, but data regarding their usage is scarce. The aim of this study was to examine the efficacy and safety of low-dose NOAC compared to single (SAPT) or dual antiplatelet therapies (DAPT) after LAAO. We included consecutive patients with non-valvular atrial fibrillation who underwent LAAO and received l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Actually, there are many other factors that affect the efficacy of LAA closure, including antithrombotic therapy. 25 , 26 As there have been no randomized controlled trials of antithrombotic therapy in LAA closure, this must be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there are many other factors that affect the efficacy of LAA closure, including antithrombotic therapy. 25 , 26 As there have been no randomized controlled trials of antithrombotic therapy in LAA closure, this must be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…60 Cepas-Guillen et al recently conducted a study in which a low-dose strategy with apixaban (2.5 mg twice daily) was tested against single antiplatelet therapy (SAPT; low-dose aspirin 100 mg once daily) and DAPT (aspirin 100 mg + clopidogrel 75 mg once daily) in patients with nonvalvular AF who underwent LAAO. 61 The authors concluded that a strategy with low-dose apixaban following LAAO might be a feasible and effective alternative to DAPT and SAPT concerning combined efficacy and safety endpoints. However, this study was not randomised and enrolled a limited number of patients.…”
Section: Continuous Oral Anticoagulant Regimen Following Left Atrial ...mentioning
confidence: 98%
“…Data from a small RCT also reported a numerically lower rate of DRT with DOAC (0%) compared to DAPT (6%) 65 . Of note, preliminary data suggested that low-(versus full-) dose DOAC could result in the same beneficial effects regarding DRT and thromboembolic protection after LAAO 75,78 . Multiple randomised trials are comparing DOAC versus DAPT following LAAO and will likely provide more definite data on the safety and efficacy of this therapy (Table 9).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…This therapy has recently been considered as a potential alternative following LAAO in patients e 1056 eligible for short-term OAC. Data from several observational studies have shown extremely low rates of DRT (0 to 1.3%, 0% in the majority of studies), and thromboembolic events in patients treated with DOAC following LAAO 23,64,65,[73][74][75][76][77][78] . Furthermore, some studies have also suggested a lower rate of bleeding events among DOAC patients compared to their DAPT counterparts 73,75 .…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%